Exploring the Impact of Citric Acid on Mitigating Sweet Potato Soft Rot and Enhancing Postharvest Quality - Yixi Chen; Linjiang Pang; Jiacheng Bai; Wenbao Yu; Yueming Zhu; Melvin Sidikie George; Zunfu Lv; Guoquan Lu (Agriculture)
Citric acid (CAC) is a ubiquitous, odorless, and non-toxic food additive. Soft rot, caused by the pathogen Rhizopus stolonifer, is a major postharvest disease affecting sweet potato (Ipomoea batatas (L.) Lam). The main theme of this study is to determine the CAC inhibitory mechanism against Rhizopus stolonifer, the causative agent of sweet potato soft rot. To ascertain the practical applicability of CAC, both in vitro and in vivo methodologies were employed. The aim of the in vitro experiments in this study was to delineate the effects of a 0.5% (w/v) CAC solution on the growth inhibition of Rhizopus stolonifer, encompassing mycelial morphology and colony expansion. In vivo experiments were carried out using “Xinxiang” sweet potato varieties and the application of a 0.5% (w/v) CAC solution as a pretreatment. Specifically, the tissue treated with 0.5% CAC maintained better appearance quality and texture characteristics; peroxidase, β-1,3-glucanase, chitinase, and phenylalanine ammonia-lyase activities were enhanced. Conversely, the same treatment resulted in a downregulation of polyphenol oxidase, catalase, ascorbate peroxidase, cellulase, and polygalactosidase activities. Moreover, CAC treatment was found to maintain elevated levels of total phenolics and flavonoids within the sweet potato tissues. In summary, the study demonstrates that 0.5% CAC fortifies the resistance of sweet potato to soft rot by activating defense-related enzymes, suppressing the activity of cell wall-degrading enzymes, and promoting the accumulation of antimicrobial compounds. These results advocate for the utilization of CAC as a postharvest treatment to mitigate the incidence of sweet potato soft rot.